Desenvolvimento de uma aplicação para automação de projetos 3D: um estudo de caso na indústria de ônibus - Busetto, Roberto (2017)
The production of bodies and buses is complex and costly, with countless sales options, budgets and sales, administrative work, suppliers and numerous production orders. These conditions, during the product's life cycle, generate exclusive products for each customer, with a high number of engineering hours. Such engineering knowledge often ends up being lost in notes and personal files, generating delays in project deliveries, unnecessary project time, rework and design errors. In this context, the present work aims to develop a computational application, integrated with Siemens NX software for 3D project automation, combining product configuration approaches with project automation techniques, in order to support product design and development activities. The approach is based on intelligent three-dimensional entities (templates) that encapsulate product configuration rules and project creation logic, absorbing the various characteristics and variations chosen by the customer, unifying product knowledge, geometries, product structure, project reuse and sales configuration. This approach is applied through a case study in a bus bodybuilder, in which two different projects were used. In the end, it was concluded that the objectives were achieved and that the application, in addition to being stable, has scalability to be used across the company's entire product line and applied directly in the Development Engineering and Product Engineering sectors.